2016
DOI: 10.1016/j.freeradbiomed.2016.03.018
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin E metabolite 13′-carboxychromanols inhibit pro-inflammatory enzymes, induce apoptosis and autophagy in human cancer cells by modulating sphingolipids and suppress colon tumor development in mice

Abstract: Vitamin E forms are substantially metabolized to various carboxychromanols including 13'-carboxychromanols (13'-COOHs) that are found at high levels in feces. However, there is limited knowledge about functions of these metabolites. Here we studied δT-13'-COOH and δTE-13'-COOH, which are metabolites of δ-tocopherol and δ-tocotrienol, respectively. δTE-13'-COOH is also a natural constituent of a traditional medicine Garcinia Kola. Both 13'-COOHs are much stronger than tocopherols in inhibition of pro-inflammato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
74
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 51 publications
(78 citation statements)
references
References 44 publications
2
74
2
Order By: Relevance
“…Meanwhile, cells treated with γTE had decreased C 16:0 -SM and total SMs throughout the treatment compared with controls. Interestingly, we have recently shown that long-chain carboxychromanols (vitamin E metabolites) caused similar temporal changes of sphingolipids in cancer cells at a faster rate than γTE [28]. The time-based alteration of sphingolipids provides clues of potential cellular target(s) of γTE and the role of specific sphingolipids in γTE-mediated anticancer effects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, cells treated with γTE had decreased C 16:0 -SM and total SMs throughout the treatment compared with controls. Interestingly, we have recently shown that long-chain carboxychromanols (vitamin E metabolites) caused similar temporal changes of sphingolipids in cancer cells at a faster rate than γTE [28]. The time-based alteration of sphingolipids provides clues of potential cellular target(s) of γTE and the role of specific sphingolipids in γTE-mediated anticancer effects.…”
Section: Discussionmentioning
confidence: 99%
“…Sphingolipids were measured by a LC-MS/MS method modified based on previous publications [27, 28]. Analyses were performed using the Agilent 6460 triple quadrupole mass spectrometer coupled with the Agilent 1200 Rapid Resolution HPLC (Agilent Technologies, Santa Clara, CA) with detection of sphingolipids in positive mode by multiple reaction monitoring (MRM) technique.…”
Section: Methodsmentioning
confidence: 99%
“…Specifically, αT‐13′‐COOH and δT‐13′‐COOH induced apoptosis in HepG2 human liver cancer cells, as indicated by activated caspase 3, 7 and 9, and PARP cleavage . We demonstrate that δT‐13′‐COOH and δTE‐13′‐COOH inhibit proliferation and induce apoptosis in HCT116 and HT‐29 human colon cancer cells, as indicated by PARP cleavage and caspase 9 activation . δT‐13′‐COOH and δTE‐13′‐COOH treatment also induced autophagy, as indicated by increased LC‐3II .…”
Section: Vitamin E Forms and 13'‐coohs Induce Apoptosis Necrosis Aumentioning
confidence: 85%
“…We demonstrate that δT‐13′‐COOH and δTE‐13′‐COOH inhibit proliferation and induce apoptosis in HCT116 and HT‐29 human colon cancer cells, as indicated by PARP cleavage and caspase 9 activation . δT‐13′‐COOH and δTE‐13′‐COOH treatment also induced autophagy, as indicated by increased LC‐3II . Interestingly, normal colon epithelial (CCD841CoN) cells appeared to be much less sensitive to δT‐13′‐COOH and δTE‐13′‐COOH treatment, suggesting selective induction of death in cancer cells .…”
Section: Vitamin E Forms and 13'‐coohs Induce Apoptosis Necrosis Aumentioning
confidence: 96%
See 1 more Smart Citation